City Branding Ambon City Of Music Sebagai Folk Identity Music Di Maluku - Aksa Noya (Institut Seni Indonesia Yogyakarta, 2020)
The article of city branding on Ambon City of Music discusses the legalisation of folk music identity in Maluku. By using the qualitative research method with a case study approach. Data obtained were primary data in the field, and the secondary data were obtained from various media. Data was collected by doing direct interviews and essential documents. Ambon City of Music is an iconic branding that becomes the identity for the people of Maluku. The people of Maluku have music DNA so that it is worth mentioning as a City of Music. It can be seen through the selection of Ambon city as a City of Music by UNESCO in October 2019. Ambon City has become a new identity to introduce the musical culture of the Maluku people. Music is used as social capital in creating peace, while the acculturation of the folk music genre is a symbol of community identity in Maluku. The author argues that the branding of Ambon City of Music itself elevates the dignity of folk music identity. The people of Maluku are known as having the highly musical skills, singing, and experts in playing traditional instruments, such as tifa, totobuang, bamboo flute, tahuri, etc. The recognition by UNESCO strengthens the musical identity of the people of Maluku in the world. Ambon city branding is a legitimation of Maluku folk identity in music and singing and a city of peace because of the music, with the result of the people of Maluku collectively having an awareness of primordial relations.